Understanding impacts of time and cost related construction risks on operational performance of PPP projects - Doloi, Hemanta (International Journal of Strategic Property Management, 2012)
The risk attributes in construction project is one of the widely published topics, yet there is no or little investigation whether or not risks associated with construction phase propagate over operational phase. As operation phase of the PPP projects is significantly long compared to the construction phase, understanding the impact of time and cost related construction risks over operation phase is quite important. In this research, risk attributes associated with the PPP procurement method have been identified across three dimensions, time, cost and operational performance. A questionnaire survey was used for collecting data in seven major PPP projects in Australia. Based on standard statistical methods and factor analysis, a number of key risk factors influencing time, cost and operational performance have been extracted. The research revealed that site conditions and design complexity is one of the most critical risk attribute influencing time performance in projects. Similarly, market dynamics is the most critical attribute influencing both construction cost and operational performance in PPP projects. Based on regression modeling, partner's dispute was found to be a good determinant of time and cost performance. Technical obsolescence has significant impacts on the operational performance of PPP projects. It was revealed that the design complexity, financial structure and government policy are the three main common factors affecting risks across time, cost and operational performance in PPP projects. It is anticipated that the findings will impact the construction firms for improving the front-end risk management capability for efficient positioning within the competitive business environment.First Publish Online: 2 Oct 2012